A study on domestic solid waste production and management in the Bisapug community (rural area) in Kuching sub-district - Eulogius, Ak Justin Rajang (Universiti Malaysia Sarawak (UNIMAS), 2005)
The study conducted on domestic solid waste (DSW) production and management in the Bisapug community (rural area) shows that the average amount of DSW generated by every household is around 1.48 kg per day or 45.9 kg per month in which each person generates around 0.30 kg of DSW per day. This figure is lesser in amount as compared to DSW generated in the urban area, e.g. 0.5 and 0.6 kg per day per person in Kuching and Selangor. With the estimated total population of 3,718 people staying in the study area, it is expected not less than 1,115.4 kg or 1.1 tonnes of DSW is generated daily. This figure contributes approximately 0.24 % of the total amount of municipal solid waste (MSW) (414.2 tonnes) received per day by the Kuching Integrated Waste Management Park (KIWMP) which is under the management of Trienekens (Sarawak) Sdn Bhd. The common types of DSW recycled in the study area are glass, metal aluminium, plastic and paper. The analysis result indicates 84 % of the villagers are aware of recycling activities and 75 % of them do carry out recycling activities. About 68 % of the respondents are not satisfied with rubbish bin provided by the waste operator. While, 80 % of them are satisfied with the collection service provided by the waste operator as it have been much improved after privatization of the collection service in term of punctuality collection and collection equipment used.